2011
DOI: 10.1111/j.1479-828x.2010.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy: A 10-year review at the Royal Hospital for Women, Sydney

Abstract: In our series, abnormal placentation causing severe haemorrhage was the commonest indication for EPH. Previous CS is a risk factor for abnormal placentation and particularly for morbid adherence of the placenta. The morbidity associated with EPH is considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
75
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 26 publications
16
75
2
4
Order By: Relevance
“…The most common complication found was intraoperative bladder injury in 21.13% of cases. This is rate is high but nearly similar to Awan et al 29 results who reported 22.6% of intraoperative urinary tract injuries in their series. A planned rather than an emergency caesarean hysterectomy in women at high risk of EPH may be associated with lower morbidity rates.…”
Section: Discussionsupporting
confidence: 75%
“…The most common complication found was intraoperative bladder injury in 21.13% of cases. This is rate is high but nearly similar to Awan et al 29 results who reported 22.6% of intraoperative urinary tract injuries in their series. A planned rather than an emergency caesarean hysterectomy in women at high risk of EPH may be associated with lower morbidity rates.…”
Section: Discussionsupporting
confidence: 75%
“…Mathuriya et al study also concluded similar results 9 .incidence of placenta previa increases with increasing age and parity 10 .Getahun D et al study concluded that there is a dose response pattern in the risk of previa with increasing no of prior cesarean section and short pregnancy interval is also associated with increased risk 11 .study by Ihab m usha et al also showed increase in rate of placenta previa with increase in no of previous cesarean 12 .various literature concluded that increasing parity increases the risk of placenta previa 13 .our study included only multigravida in order to avoid biass. Placenta previa poses more risk of complications like PPH and its surgical treatments cesarean hysterectomy and operative morbidity are more in case group 14,15 . In present study all cases of adherent placenta seen in previous cesarean which is consistent with Clark etal study 16 .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8]11,12,22,24,25] In middle-income countries the aetiology is variable, with studies from Turkey, India and Thailand showing similar indications to high-resource settings but with higher rates of uterine rupture. [4,15,16,21,[26][27][28] Sepsis has been reported as an indication in low-resource settings.…”
mentioning
confidence: 99%
“…Definitions include a hysterectomy performed within 24 hours of delivery, [2][3][4][5] a hysterectomy performed within the same hospitalisation, [6][7][8][9][10] a hysterectomy performed within 72 hours of delivery, [11] a hysterectomy performed within 1 month of delivery [12,13] to a hysterectomy performed within 6 weeks of delivery. [14] Some even limit the definition to a hysterectomy performed for uncontrolled haemorrhage only [4,[15][16][17][18][19][20][21][22] and exclude cases of infection.[12] The varying definitions make it difficult to compare incidences and aetiology. If a short time period after delivery is used, complications related to sepsis and delayed haemorrhage may be underestimated.…”
mentioning
confidence: 99%